ANALISIS TEOLOGIS TERHADAP PEMAHAMAN ONENESS PENTECOSTAL TENTANG TUHAN MELALUI LENSA PENGAKUAN IMAN OIKOUMENIS - Marpaung, Welko; Fransisco, Vido (Jurnal Teologi Amreta (ISSN: 2599-3100), 2024)
The Pentecostal Oneness’ view of God significantly deviates from thedoctrine of the Trinity. However, it is precisely this concept ofunderstanding that most of Trinitarian Pentecostal Christians indirectlyunderstand the concept of the Godhead. Oneness Pentecostals reject theconcept of the Trinity by teaching that God is one person revealed in JesusChrist, with no personal distinction between the Father, Son, and HolySpirit. This rejection creates fundamental theological differences thataffect Christians' understanding of the nature of God. This study aims toanalyze the Pentecostal Oneness’ doctrine of God through the lens of theoikoumenical creeds, which represents the Trinitarian view. The resultsshow that the Pentecostal Oneness teaching carries theologicalimplications that contradict the doctrine of the Trinity affirmed in theOikoumenical Creeds. Through theological analysis, it was found that thedoctrine of Oneness misleads Trinitarian Pentecostal Christians' view ofGod, which should be understood within the framework of the Trinity. Thisresearch emphasizes the significance of maintaining the doctrine of theTrinity and provides direction for the churches to respond appropriately tothe Pentecostal Oneness teaching to avoid distortion in theologicalteaching.